2017
DOI: 10.1386/jaac.9.2.109_1
|View full text |Cite
|
Sign up to set email alerts
|

The role of participatory arts in addressing the loneliness and social isolation of older people: A conceptual review of the literature

Abstract: Loneliness and social isolation are pertinent issues for older people due to the life transitions and loss often experienced in later life. Research points towards the potential for participatory arts with older people to address loneliness and social isolation; however, there is little conceptualization of the mechanisms through which this can be promoted. This conceptual review brings together selected literature that reports on the social impacts of participatory arts with older people to develop a conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 0 publications
1
16
2
Order By: Relevance
“…Our findings show that over 80% of the respondents reported that their engagement in the arts makes them feel socially connected at least ‘a little’. This finding is expected given the previously cited evidence that the arts can support social connections, although the evidence base to date has been most extensive in research with older adults [ 17 20 ]. This study extends the evidence base through a wider sample, based on key demographics of the adult UK population and representing a much wider range of adult age groups.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Our findings show that over 80% of the respondents reported that their engagement in the arts makes them feel socially connected at least ‘a little’. This finding is expected given the previously cited evidence that the arts can support social connections, although the evidence base to date has been most extensive in research with older adults [ 17 20 ]. This study extends the evidence base through a wider sample, based on key demographics of the adult UK population and representing a much wider range of adult age groups.…”
Section: Discussionmentioning
confidence: 77%
“…Review articles, while pointing out limitations in the evidence base such as inconsistency in measurement tools and reporting of results [ 16 ], suggest that engagement in the arts can particularly support older adults. Dadswell and colleagues, for example, report a conceptual review indicating that participatory arts can strengthen and build relationships through social interaction, tackle inconsistences between expected and real relationships through enhancing self-worth and feelings of belonging, and allow older adults to contribute inclusively to their community [ 17 ]. Similarly, a review of forty-four studies indicated that participatory arts can promote reciprocal relationships among older adults, care givers, and the wider community [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Loneliness and social isolation are clearly linked, but do not always present together; for example, a person may be isolated due to a small network but protected against loneliness by a few deep and meaningful relationships. 3 The direct consequences of loneliness are both social and emotional, 4 , 5 but loneliness and social isolation can also be detrimental to health, wellbeing and quality of life. 6 A recent literature review found the most prevalent health outcome of loneliness in old age was depression, while for social isolation it was cardiovascular problems.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of the literature identified that the arts promoted a sense of belonging to an artistic community and contentment with social lives, addressing discrepancies between desired relationships and reality. 3 Arts also facilitated interactions and enhanced social capital, helping to strengthen existing relationships and build new ones. Finally, arts enabled older people of all capacities to engage in meaningful social participation and make a valued contribution to their relationships and communities, indicating the potential of participatory arts to alleviate loneliness and social isolation experienced in care homes.…”
Section: Introductionmentioning
confidence: 99%
“…This focus is even more apparent in review articles and large-scale epidemiological studies. Indeed, reviews have indicated that participatory arts can strengthen and build relationships [ 51 ] and promote reciprocal relationships among older adults, care givers, and the wider community [ 52 ]. Community-engaged art programs have been seen as promising for addressing loneliness in older adults [ 53 ].…”
Section: Introductionmentioning
confidence: 99%